The Effect of Ten-Block Based Media on The Mathematics Learning Outcomes of Grade 2 Students of MI PSM Al-Amin Sumber Agung - Wahyu Tri Yatna Shandika; Aulia Fajar Khasanah; Miratu Chaeroh (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Low mathematics achievement among elementary school students remains a persistent educational challenge, primarily due to the predominance of abstract instructional methods and the limited integration of concrete learning media. This issue was also identified among second-grade students at MI PSM Al-Amin Sumber Agung, where approximately 50% of students failed to achieve the Minimum Mastery Criterion (MMC) in mathematics. This study aimed to examine the effect of implementing Base Ten Blocks supported by an LCD projector on students' mathematics learning outcomes. A quantitative approach with a quasi-experimental method employing a Nonequivalent Control Group Design was adopted. The study involved 38 second-grade students selected through a saturated sampling technique, comprising 24 students in Class II A as the experimental group and 14 students in Class II B as the control group. Data were collected using validated and reliable pretest and posttest achievement tests. Statistical analyses included tests of normality, homogeneity of variance, and an Independent Samples t-test using SPSS version 24. The findings confirmed that the data satisfied the assumptions of normality and homogeneity. Hypothesis testing yielded a significance value (Sig. 2-tailed) of 0.000 (< 0.05), indicating a statistically significant difference between the two groups and supporting the alternative hypothesis. Moreover, the experimental group obtained a higher mean posttest score (81.25) than the control group (67.86). These findings demonstrate that the integration of Base Ten Blocks with LCD projector-assisted instruction significantly enhances students' understanding of place value and arithmetic operations, encourages active classroom participation, and improves overall mathematics learning outcomes.